2020
DOI: 10.1002/jts.22515
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health, Psychological Distress, and Coping in Australian Cross‐Cultural Prison Populations

Abstract: The rates of mental illness are significantly higher in prison populations compared to the general community; however, little research has examined the rates of mental illness for cross‐cultural groups of prisoners in Australia. This omission is concerning given the increasingly diverse nature of the Australian prison population. To address this gap in knowledge, the present study aimed to identify rates of key mental health factors and associated psychological processes in a cohort of 191 men from culturally … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 48 publications
1
6
0
Order By: Relevance
“…Another study conducted among prison inmates in Victoria, Australia further strengthened the findings of the current study that it shows use of positive thinking as a coping strategy predicted a decrease in psychological distress level (Rose et al, 2020). Few other research as also indicated that positive thinking has helped the individuals to deal with stressful situations to improve the psychological status (Shulman & Cauffman, 2011;Van Harreveld, et al, 2007).…”
Section: Engaging In Religious Activitiessupporting
confidence: 77%
“…Another study conducted among prison inmates in Victoria, Australia further strengthened the findings of the current study that it shows use of positive thinking as a coping strategy predicted a decrease in psychological distress level (Rose et al, 2020). Few other research as also indicated that positive thinking has helped the individuals to deal with stressful situations to improve the psychological status (Shulman & Cauffman, 2011;Van Harreveld, et al, 2007).…”
Section: Engaging In Religious Activitiessupporting
confidence: 77%
“…This allows us to assume that people in penitentiary units who experience strong stress feel helpless in the face of their life situation. The feeling of helplessness is a negative phenomenon associated with the occurrence of increased mental tension, which may lead to the occurrence of depressive disorders among prisoners and, consequently, to attempting suicide [ 35 , 46 , 47 , 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
“…The research indicates that among detainees, stress-related diseases are diagnosed more often than in the general population (Bronson and Berzofsky, 2017; Clarke and Waring, 2012; Houle, 2014; Massoglia and Pridemore, 2015; Howell et al , 2016). Analysis of the available literature has shown that research dealing with the issue of stress and emotions among detainees are carried out with the use of various, often non-standardised or original research tools, which makes reliable comparison of results difficult (Unver et al , 2013; Reta et al , 2020; Chiclana et al , 2019; Constantino et al , 2016; Baidawi, 2016; Rose et al , 2020; van den Berg et al , 2016; Ahmad and Mazlan, 2014; Malik et al , 2019; Joon Jang, 2020). This provided the motivation to explore the above issue using standardised and reliable research tools.…”
Section: Discussionmentioning
confidence: 99%